Heterologous Dimension of the Other Sociality in the Cognitive Space of Uncertainty - Zhussupova, B.Zh.; Karipbayev, B.I.; Zhumassultanova, G.A.; Umurkulova, M.M. (Integrative Psychological and Behavioral Science, 2023)
Contemporary society is presented as a model of other sociality demanding extraordinary methods of research in the cognitive space of uncertainty. This article aims at analyzing a heterologous paradigm of postnon-classical social philosophical discourse and how it applies to the socio-philosophical context of modernity by using cognitive and heuristic capabilities of social heterology which explain the uncertainty principle of social cognition in other sociality. The diversity of the other sociality is characterized by structural non-linearity, disequilibrium, rupture, decentralism, and lack of a unified systematic principle. In their research, authors highlighted the two different approaches to analyzing the social structure: the classical ontological and post-non-classical heterologous one. Philosophical and scientific sources of European and Russian traditions were used to suggest new revolutionary post-non-classical methods and social paradigms emphasizing the heterogeneous pattern of contemporary, unexpected and even unpredictable society. Transition to social heterogeneity is attributed to the uncertainty principle in extraordinary processes of social self-development. The authors’ position is that the heterologous dimension of sociality approaches the complete understanding of social life’s contradictions of a modern human not only in a cognitive perspective but also in a practical one to define humanistic social policy.
Keywords: Other sociality; Uncertainty; Heterogeneous pattern; Post-nonclassical methods; Modern society; Decentralism